The service industries in a developing economy; Israel as a case study - Ofer, Gur. (New York, Published in cooperation with the Bank of Israel by Praeger, 1967)
This book is about economic structure-the industrial distribution of national product and of labour force and other input
"An early version ... was submitted to the Hebrew University, Jerusalem, as an M. A. thesis ... written during 1963 and 1964."
Bibliography: p. 157-158.
oo 4/10/18
Loans
Keywords: Service industries